Identification of GATA Transcription Factors in Brachypodium distachyon and Functional Characterization of BdGATA13 in Drought Tolerance and Response to Gibberellins - Guo, Jie; Bai, Xionghui; Dai, Keli; Yuan, Xiangyang; Guo, Pingyi; Zhou, Meixue; Shi, Weiping; Hao, Chenyang (Frontiers in Plant Science, 2021)
GATA transcription factors (TFs) are type IV zinc-finger proteins that have roles in plant development and growth. The 27 GATA TFs identified in the Brachypodium distachyon genome in this study were unevenly distributed across all five chromosomes and classified into four subgroups. Phylogenesis-related GATAs shared similar gene structures and conserved motifs. Expression profiles showed that all BdGATA genes were expressed in leaves and most were induced by PEG treatment. BdGATA13 was predominantly expressed in leaf tissue and phylogenetically close to OsSNFL1, AtGNC, and AtGNL. Its protein was detected in the nucleus by subcellular localization analysis. Overexpression of BdGATA13 in transgenic Arabidopsis resulted in darker green leaves, later flowering, and more importantly, enhanced drought tolerance compared to the wild type. BdGATA13 also promoted primary root development under GA treatment. These results lay a foundation for better understanding the function of GATA genes in B. distachyon and other plants.